A Culture–Behavior–Brain Loop Model of Human Development. Issue 11 (November 2015) - Han, Shihui; Ma, Yina
Abstract : Increasing evidence suggests that cultural influences on brain activity are associated with multiple cognitive and affective processes. These findings prompt an integrative framework to account for dynamic interactions between culture, behavior, and the brain. We put forward a culture–behavior–brain (CBB) loop model of human development that proposes that culture shapes the brain by contextualizing behavior, and the brain fits and modifies culture via behavioral influences. Genes provide a fundamental basis for, and interact with, the CBB loop at both individual and population levels. The CBB loop model advances our understanding of the dynamic relationships between culture, behavior, and the brain, which are crucial for human phylogeny and ontogeny. Future brain changes due to cultural influences are discussed based on the CBB loop model. Trends: Cultural neuroscience research combines cultural psychology, brain imaging, and genetics to investigate whether and how cultural contexts/experiences interact with genes to shape the functional organization of human brain and behavior. Cultural neuroscience findings suggest indirect culture–brain interactions, through practice of behaviors, and direct culture–brain interactions, which constitute an interacting loop that provides a basis of human development. The CBB loop model of human development considers different timescales along which genes and culture interact with the brain and behavior, and highlights genetic interactions with the CBB loop. The CBB loop model can be used to predict future brain changes.